ASPECTS OF ADJECTIVAL SECONDARY PREDICATION IN MACEDONIAN (Journal of Contemporary Philology, 2019)
The  paper  discusses the  basic  features  of  the  adjectival  secondary  predication  in Macedonian.  It  focuses  on  several  aspects,  especially  on  the  semantic,  syntactic and information structure character of the secondary predicates. In that regard, the paper points out their basic meanings, the relation between the thematic structure and their position in the utterance, as well as the reasons for their embeddedness or non-embeddedness in the prosodic structure. Several features are detected: the temporal and thecausal character of their relation with the primary predication; the cases in which they occur within or out of the informational core (in the zone right or left from the predicate); the implications of their informational character regard-ing the position; and the reflection of the difference between depictive secondary predicates and adjectives expressing longstanding characteristics. The analysis is carried out, mainly, by drawing on examples collected from literary works by several Macedonian authors.
Keywords: adjective; secondary predication; depictive; meaning; position